متطلبات نجاح مكافحة الفساد و الفقر في الجزائر في ظل الحوكمة - مهديد, فطيمة; حاجي, فطيمة (Université de M'sila, 2016)
The corruption and poverty of the biggest challenges facing the world today, especially in light of the growing taking the principles of governance, and Algeria did not pay much attention to the fight against corruption and poverty in the beginning of economic reforms, but with the escalation of their unit and the emergence of negative on society, has become a concern to fight corruption and poverty is constantly increasing, so she a series of reforms since the nineties, and with the third millennium solutions adopted Algeria several policies to eliminate these phenomena, and have these reforms have contributed to the reduction of these phenomena but did not eliminate them entirely because of the range of challenges that still face the fight against corruption and poverty.